I CAN BUY MYSELF FLOWERSâ€: A Gender Performativity Analysis of Women's Empowerment in Miley Cyrus's Flowers - Stefi Nania Tampubolon; Nur Halfa Nabila; Syarifah Sarah Nurjihan; Nurlaili Fitria; T. Thyrhaya Zein (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study analyzes the representation of women's empowerment in Miley Cyrus's song "Flowers"(2023) and its contribution to the discourse of self-love and female independence from a feministperspective. Employing an exploratory-interpretive qualitative research design, the study uses JudithButler's theory of gender performativity as the analytical framework. The primary data consist of thecomplete song lyrics, which were analyzed using the interactive model of Miles et al. (2014) andCreswell's (2014) qualitative analysis procedures. The findings reveal that women's empowermentis represented through repeated self-directed actions expressed in the phrase "I can," whichemphasizes agency, emotional self-reliance, and personal autonomy. The lyrics further portray selflovethrough acts of self-care, self-acceptance, and forgiveness, while also representing femaleindependence through the speaker's ability to define herself beyond romantic relationships. FromButler's perspective, these repeated actions function as performative acts through which the femalepersona continuously reconstructs her identity. Furthermore, the song contributes to contemporarydiscussions of self-love and women's empowerment by promoting emotional resilience andindependence following a romantic breakup. The values represented in the song also support thebroader objectives of Sustainable Development Goal 5 (Gender Equality) by encouraging women'sautonomy, self-determination, and empowerment. This study contributes to feminist literary studiesby demonstrating how popular song lyrics can function as cultural texts that foster gender awarenessand empowerment in contemporary society.Keywords: feminism, women's empowerment, song lyrics, self-love, gender performativity,popular music